Lost in time and space: temporal and spatial challenges facing older workers in a global economy from a career capital perspective - Tempest, Susan; Coupland, Christine (Taylor and Francis, 2016)
This paper develops a conceptual framework to enhance our understanding of the career challenges facing older workers in a global economy. A distinction between ‘high’ and ‘low’ career capital of older workers is made. This distinction is then used to highlight potential temporal and spatial challenges for older workers in their later life careers. We draw on empirical evidence from existing studies of older workers and their careers. The contribution of this paper to human resource management debates is threefold. Firstly, we contribute to debates in the HRM(Human Resource Management) literature about intelligent careers and career capital by distinguishing between high and low career capital to explain the polarisation of older workers’ careers. Secondly, we synthesise career capital issues with spatial and temporal aspects of international labour markets to conceptualise the key issues and challenges which create potential boundaries for older workers when navigating later life careers thereby contributing to ‘boundary-focused scholarship’ (Inkson, K., Gunz, H., Ganesh, S., & Roper, J. (2012). Boundaryless careers; Bringing back boundaries, Organization Studies, 33, 323–340). Finally, we develop a series of propositions to provide a basis for further research into the issues of space and time relevant to older ‘high’ and ‘low’ career capital workers, their careers and HRM.